Answer:
3n + 2
Step-by-step explanation:
-n+(-4)-(-4n)+6
= -n -4 +4n +6 [positive plus negative = negative; ∴ +(-4) = -4
=4n - n +6 - 4 negative plus negative = positive; ∴ -(-4n) = 4]
now subtract n from 4n and subtract 4 from 6
=3n + 2
Answer:
Clara Barton- founder of the American Red Cross
Sally Tompkins- fought for equal pay
James Henry Gooding- established a war hospital
Hope This Helps! Have A Nice Night!!
Answer:
The Length of <em>JK</em> is 10
Step-by-step explanation:
Because <<em>J </em>is congruent to <<em>L</em> we know that the triangle in question must be isosceles as in an isosceles triangle two angles opposite of each other are equal. (This is also true for equilateral triangles, however, in an equilateral triangle all sides must be congruent, so we can rule equilateral out as <em>LJ </em>is not congruent to <em>KL.) </em>This means that the triangle must be isosceles.
In an isosceles triangle the side opposite each other are congruent, and the angles opposite each other are congruent when split down the line of symmetry.
Therefor, the length of <em>JK </em>must be congruent to the length of <em>KL. </em>In other words if <em>JK </em>= 10, then <em>KL </em>must equal 10 as well.
Answer:
−
6
=
3
7
n
Step-by-step explanation:
Rewrite the equation as
3
7
n
=
−
6
.
3
7
n
=
−
6
Multiply both sides of the equation by
7
3
.
7
3
⋅
3
7
⋅
n
=
7
3
⋅
−
6
Simplify both sides of the equation.
Tap for more steps...
n
=
−
14
1) First find the multiplier.
Look at the 0 and 1st term you have 5 as the 0 and 3 as the 1st term.
2)Ask how do we get from 5 to 3?
- We subtract 2 so the multiplier is -2
3)Lets make a linear equation: y=mx +b
- m= multiplier or slope
- x= Just equals x value
- b= your starting value or the 0 term which is 5
4)Use the values that you have to create your equation.
Note:For the x value just plug in the x value from your table.
Ex.